Nutrition Management in Pediatric Traumatic Brain Injury: An Exploration of Knowledge Gaps and Challenges - Chowdhury, Sumit Roy; Sahu, Priyanka; Bindra, Ashish (Journal of Neuroanaesthesiology and Critical Care, 2024)
Traumatic brain injury (TBI) stands as the leading cause of morbidity and mortality among children, as evidenced by the most contemporary statistics. Undernutrition in pediatric TBI (PTBI) leads to increased mortality, heightened infectious complications, and more severe neurological consequences. Therefore, timely and effective nutritional therapy is crucial in managing PTBI to improve patient prognosis and outcomes. Limited investigations have been conducted on the nutritional requirements specific to these patients and management often relies on data from adults with TBI for guidance. We have meticulously searched different databases to compile a broad range of the most up-to-date clinical research. This review analyses the challenges associated with providing nutritional support to children with TBI and provides a clearer understanding of the current evidence-based recommendations for optimal nutritional therapy. The review primarily focuses on recommendations and suggestions for energy requirements, nutritional assessment, initiation of nutrition, various feeding methods offered, identification of malnutrition, the impact of malnutrition on patient outcomes, and areas of further research.
Keywords: pediatric traumatic brain injury; nutrition support; enteral nutrition; malnutrition; nutritional assessment